Voices of English education department teachers on traces of neoliberal ideology in the ‘Kampus Merdeka’ concept - Endro Dwi Hatmanto; Bambang Widi Pratolo; Eko Purwanti (International Journal of Evaluation and Research in Education (IJERE), 2023)
Neoliberal ideology’s influence on higher education has been a concern for researchers on a global scale. Indonesian researchers have also examined the practice of neoliberalism in higher education. However, they only focused on the managerial dimension and there is a dearth of literature on the influence of neoliberalism ideology on educational policy. This study intends to close a gap in earlier studies by investigating the ideological remnants of Neoliberalism in the notion of ‘Kampus Merdeka’ or Emancipated Learning as perceived by 12 lecturers at English Education Department in Yogyakarta. This study employed a qualitative approach through the use of semi-structured interviews. The study found that university and departmental missions were aligned with industry demands; the curriculum was driven by industry; the teaching and learning process was determined by the market; the Tridharma of Higher Education was extended to industry; little emphasis was placed on moral and religious values; curriculum “vocationalization” was emphasized; collaboration with industry was focused; academic commodification and consumerism increased; and academic commodification and consumerism accelerated. The findings added to a new existing theme, that is increased collaboration with industry. Moral and religious values must be incorporated into the curriculum, as they are absent in ‘Kampus Merdeka’ paradigm.